Topologies as Techniques for a Post-Critical Rhetoric - Walsh, Lynda; Boyle, Casey (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book restores the concept of topology to its rhetorical roots to assist scholars who wish not just to criticize power dynamics, but also to invent alternatives. Topology is a spatial rather than a causal method. It works inductively to model discourse without reducing it to the actions of a few or resolving its inherent contradictions. By putting topology back in tension with opportunity, as originally designed, the contributors to this volume open up new possibilities for post-critical practice in "wicked discourses" of medicine, technology, literacy, and the environment. Readers of the volume will discover exactly how the discipline of rhetoric underscores and interacts with current notions of topology in philosophy, design, psychoanalysis, and science studies. .
Keywords: Social sciences.; History.; Philosophy and science.; elektronické knihy; electronic books